1993
DOI: 10.1111/j.1651-2227.1993.tb12918.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of recombinant human insulin‐like growth factor I given subcutaneously to healthy volunteers and to patients with growth hormone receptor deficiency

Abstract: The pharmacokinetics of recombinant human insulin-like growth factor I (rhIGF-I) were studied in healthy volunteers and in patients with growth hormone receptor deficiency (GHRD; Laron syndrome). Following single subcutaneous injections of rhIGF-I, 40 and 80 micrograms/kg, to healthy volunteers, the peptide was absorbed slowly, with a maximum concentration reached after about 7 hours. Following daily multiple subcutaneous injections of rhIGF-I, 40 micrograms/kg, trough concentrations of IGF-I were increased by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
2
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 13 publications
1
26
2
1
Order By: Relevance
“…However, in our study, a single intramuscular PRGF or HPRGF injection at clinical doses did not result in an increase in circulating IGF-1 levels in any of the test periods. This could be because most of the PRP systems do not concentrate IGF-1 (Schippinger et al 2011); in addition, IGF-1 in plasma has a low half-life (20 h) in humans (Grahnen et al 1993) and, although we could not find published data, in dogs should be similar. Our results differ from those in a previous study, in which serum levels of IGF-1 increased for 48 h after a PRP-derivate injection, although their product contained a high number of leukocytes (Wasterlain et al 2013).…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…However, in our study, a single intramuscular PRGF or HPRGF injection at clinical doses did not result in an increase in circulating IGF-1 levels in any of the test periods. This could be because most of the PRP systems do not concentrate IGF-1 (Schippinger et al 2011); in addition, IGF-1 in plasma has a low half-life (20 h) in humans (Grahnen et al 1993) and, although we could not find published data, in dogs should be similar. Our results differ from those in a previous study, in which serum levels of IGF-1 increased for 48 h after a PRP-derivate injection, although their product contained a high number of leukocytes (Wasterlain et al 2013).…”
Section: Discussioncontrasting
confidence: 51%
“…Some authors have reported an inflammatory response, but such a response could be due to the presence of white blood cells in the preparation (Grahnen et al 1993). For our PRGF protocol, we completely discarded the plasma fraction containing white blood cells.…”
Section: Discussionmentioning
confidence: 99%
“…We used two different doses of rhIGF-I, and examination of the kinetics of the IGF system indicated that this patient's IGF-I pharmacokinetic parameters were similar to those reported in healthy subjects (11). This is in marked contrast to the 5-to 7-h IGF-I half-lives reported in GHinsensitive children (11,12). Guler et al (24), using bolus injections of [ 125 I]IGF-I and -II, demonstrated that the 150-kDa complex is responsible for the relatively long half-life of IGFs and that the 50-kDa and free IGF pool has a rapid turnover.…”
Section: Discussioncontrasting
confidence: 50%
“…These studies have demonstrated good growth responses to rhIGF-I therapy in these patients using doses in the range of 80 -120 g/kg, twice daily, which maintained appropriate circulating IGF-I levels. Pharmacokinetic studies after single sc injections independently of the dose used have shown a significantly reduced IGF-I half-life (11,12), possibly due to the marked reduction in serum IGFBP-3 and ALS found in these patients. The aim of this study was to investigate the effect of rhIGF-I therapy on the GH-IGF axis given to a patient with partial deletion of the IGF-I gene.…”
Section: Nsulin-like Growth Factor I (Igf-i) Deficiency May Arisementioning
confidence: 99%
“…Although most subjects did not experience sufficient catch-up growth in order to reach their target height, it seems that they achieve adult heights significantly taller than expected in the absence of rhIGF-I therapy [21]. A possible explanation for the reduced biological effect of rhIGF-I is the pharmacokinetics of this compound [22]. Grahnen et al [22] analyzed clearance and half-life values in both healthy controls and patients with classical GHIS.…”
Section: Discussionmentioning
confidence: 99%